Sensing Mountains Innsbruck Summer School of Alpine Research 2022 - Close Range Sensing Techniques in Alpine Terrain - Rutzinger, Martin; Anders, Katharina; Bremer, Magnus; Eltner, Anette; Höfle, Bernhard; Lindenbergh, Roderik; Mayr, Andreas; Oude Elberink, Sander; Pirotti, Francesco; Scaioni, Marco; Tolksdorf, Hanna; Zieher, Thomas (innsbruck university press, 2022)
Sensing mountains by close-range and remote techniques is a challenging task. The 4th edition of the international Innsbruck Summer School of Alpine Research 2022 - Close-range Sensing Techniques in Alpine Terrain brings together early career and experienced scientists from technical-, geo- and environmental-related research fields. The interdisciplinary setting of the summer school creates a creative space for exchanging and learning new concepts and solutions for mapping, monitoring and quantifying mountain environments under ongoing conditions of change.